«Video meliora proboque, deteriora sequor». Errors of Assessment in the Epicurean Ethics - Repici, Luciana (ΠΗΓΗ/FONS, 2020)
The paper is focused on the reasons why in the Epicurean conception men are induced into errors of assessment about the criterion to be adopted for the achievement of the ultimate good; they, in fact, behave with the result to be unsatisfied and unhappy. To what extent are voluntary and involuntary aspects involved in such a circumstance? Moreover, to what extent can a disabling condition in the body and/or a strong emotional tension in the soul affect the decision? And finally how can we avoid mis-assessments of this type or, on the contrary, make the provision to achieve the ultimate good with the appropriate choices? Literary surveys show that in Epicurus and his school the degree of awareness of these problems is high and that the solutions offered are part of a conceptual framework consistent with the foundations of Epicurean philosophy and its ethical proposal.